(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Enterprises may achieve success and growth via Customer Relationship Management (CRM). In the retail sector, customer relationship management (CRM) helps businesses learn more about their customers and create stronger bonds with them. Maintaining a dominant position in your industry requires a focus on customer loyalty. The assessment, reward, and campaign mantras may be used to achieve this. An attempt was made to examine the impact of customer relationship management on retail customer happiness and loyalty in this study using customer happiness and customer trust as intermediary variables, this paper investigated if there are relationships between relationship marketing and client loyalty. Examining customers’ views of customer satisfaction and their faith in the honesty and dependability of their exchange partners, the research sought to identify the elements that impact consumers’ trust in banking services. The results showed that relationship marketing strategies had a significant impact on customer loyalty by increasing trust and satisfaction. Customer loyalty is built on an organization-wide strategy that banks have put in place to manage and nurture their engagement with customers and sales prospects.